Summation of Powers in Open Resonator with Slotted Coupling Elements - Kuzmichev, I.; Muzychishin, B. I.; Popkov, A. Y. (Advanced Electromagnetics, 2021)
The paper analyzes the summation of the powers of two sources in a hemispherical open resonator (OR) during its tuning. The first higher axially asymmetric TEM10q oscillation mode is excited in the resonator. A circuit with an E- tee waveguide is proposed, which makes it possible to research the summation of the powers using a Gunn diode. Studies of the conducting part of the millimeter range have been undertaken. It is shown that the coefficient of powers summation of two sources in the OR using slot coupling elements does not exceed 72%. The use of one H- polarized diffraction grating, which is in the resonator, does not lead to a significant increase in the summation coefficient when moving it. This is due to the excitation of the first type of TEM10q oscillations in the resonator.